The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/bjd.16186
|View full text |Cite
|
Sign up to set email alerts
|

British Association of Dermatologists’ guidelines for the investigation and management of generalized pruritus in adults without an underlying dermatosis, 2018

Abstract: SummaryPruritus (or itch) is a common and distressing symptom of many skin diseases, systemic illnesses and psychological disorders. Itch is perhaps the commonest presenting symptom of skin disorders. In any two week period, 8 to 9% of the population suffer from significant pruritus. The focus of this guideline is not itchy rashes, but rather the situation where itch is present without rash. The guidelines also do not cover itch in children, in pregnancy, nor do they detail the science of the cause of itch. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
34

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(113 citation statements)
references
References 240 publications
2
77
0
34
Order By: Relevance
“…These real‐world data are in agreement with recent guidelines for the investigation and management of generalized pruritus without rash, which recommend investigation for the JAK2 V617F in patients with a raised haemoglobin and/or haematocrit . From a molecular diagnostics perspective, which patients to screen for the JAK2 V617F and other MPN‐associated rearrangements and mutations requires careful consideration in order to optimize laboratory resources .…”
supporting
confidence: 80%
“…These real‐world data are in agreement with recent guidelines for the investigation and management of generalized pruritus without rash, which recommend investigation for the JAK2 V617F in patients with a raised haemoglobin and/or haematocrit . From a molecular diagnostics perspective, which patients to screen for the JAK2 V617F and other MPN‐associated rearrangements and mutations requires careful consideration in order to optimize laboratory resources .…”
supporting
confidence: 80%
“…Dear Editor , Chronic pruritus (CP) is a frequent symptom that poses special diagnostic and therapeutic challenges for dermatologists. To identify the causes underlying CP, a comprehensive multidisciplinary assessment is necessary . CP can impair quality of life and can be associated with clinically relevant depression and anxiety levels; also, psychiatric comorbidity can be present independent of CP, but it may affect its dermatological management .…”
Section: Comparison Of Patients With Chronic Pruritus (Cp) With and Wmentioning
confidence: 99%
“…Generalized pruritus can be associated with underlying medical diseases or may be deemed idiopathic . Regarding idiopathic pruritus, guidelines published by the British Association of Dermatologists state that ‘Various systemic treatments have been used … However, no RCTs [randomized controlled trials] have found any one therapy to be effective and safe’ . Novel topical agents such as crisaborole are safer than long‐term use of corticosteroids, but many patients require systemic therapy .…”
Section: Clinical Characteristics Of Two Patients With Chronic Idiopamentioning
confidence: 99%